PENGARUH FAKTOR KARAKTERISTIK SOSIODEMOGRAFI TERHADAP PENGETAHUAN TENTANG OBAT GENERIK - Nurul Mardiati; Depy Oktapian Akbar (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
The policy of using generik drugs has become one of the implications expected by the Government of Indonesia through the National Health Insurance program (JKN). Because through the JKN program all health facilities are required to refer to the National Formulary (Fornas) which in fact is mostly generik drugs. Long before the JKN program was rolled out by the Government, in fact the Government had issued various policies to continue to encourage the use of generik drugs. However, so far, the use of generik drugs in Indonesia in general only has a market of around 7% compared to branded generik drugs. Bad knowledge of generik drugs can make the number of generik drugs used in the community difficult to increase. The research objective is to identify the influence of sociodemographic factors on knowledge about generik drugs. The research design is descriptive-analytic. The study used a cross sectional survey design. The method of sampling is done by proportional stratified random sampling. The method of collecting data is done by survey using a checklist questionnaire in two answer choices, namely right and wrong. Data analysis was carried out by unvariate analysis (descriptive statistics) and bivariate t test (chi-square, alternative test of kolmogorov-smirnov). The results showed that knowledge about generik drugs was influenced by the level of education, the level of income per month and the main source of drug information.